From Flagship to Flotilla? Findings from a Review of Literature on Learning Spaces in Higher Education, and Education for Sustainable Development - Claire McAvinia (Irish Journal of Academic Practice)
The development of physical and digital teaching and learning spaces in higher education has been the focus of attention from researchers in recent years. Teaching spaces on campus, and the campus itself, have been reconsidered in light of pedagogical, technological, political, ecological, and social changes influencing higher education over the past three decades. Spaces are historically under-researched in higher education, and the area is under-theorised with a failure to recognise space as a mediator of learning. The closure of most campuses during the COVID-19 pandemic prompted some reconsideration of the mediating role of physical and virtual learning spaces in higher education but there is little evidence of change or adaptation for resilience. Neither has research discussed in detail the connections with the United Nations Sustainable Development Goals (SDGs) and education for sustainable development. This paper presents an analysis of the literature on teaching and learning spaces in higher education and considers potential implications in relation to Education for Sustainable Development (ESD). Evidence indicates that socio-material frameworks would be valuable in evaluating uses of space, and that more stakeholders – particularly students – need to be involved in planning, designing, and evaluating spaces for teaching and learning. The findings point to a need for multiple smaller and more flexible spaces. The paper proposes that higher education stakeholders should reconsider large-scale campus ‘flagship’ expansion with inherently high embodied carbon, in favour of a sustainable ‘flotilla’, repurposing existing spaces on and off-campus.